Internet Use and Mental Health: Evidence from a Global Panel of 189 Countries - Cavalcanti, Bianca; Hemsley, Pedro; Moraes, Flavio (Advances in Social Sciences Research Journal, 2024)
This paper examines the relationship between internet use and mental health outcomes, focusing on anxiety and depression across 189 countries from 1990 to 2017. Using fixed effects panel regressions, we find a positive and statistically significant association between internet penetration and anxiety prevalence, with evidence of diminishing marginal effects. For depression, the results are less consistent, with significance only in specific model specifications. Robustness checks using lagged internet penetration and alternative model specifications reinforce the main findings. The results highlight the potential mental health costs of increased internet use, particularly in low-income countries where the effects are most pronounced. These findings underscore the need for policy interventions to promote healthy internet usage and mitigate potential negative mental health impacts.